Reliability of serological tests for COVID-19: comparison of three immunochromatography test kits for SARS-CoV-2 antibodies. Issue 9 (September 2020) - Fujigaki, Hidetsugu; Takemura, Masao; Osawa, Michiko; Sakurai, Aki; Nakamoto, Kentaro; Seto, Koichi; Fujita, Takashi; Hata, Tadayoshi; Akiyama, Hidehiko; Doi, Yohei; Saito, Kuniaki
Abstract: Background: Several immunochromatographic serological test kits have been developed to detect severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2)-specific antibodies, but their relative performance and potential clinical utility is unclear. Methods: Three commercially available serological test kits were evaluated using 99 serum samples collected from 29 patients diagnosed with coronavirus disease 2019 (COVID-19) and 100 serum samples collected from 100 healthy volunteers in 2017 as negative controls. Results: The specificity of the IgM and IgG antibodies showed comparable results among the three immunochromatographic serological test kits. The specificity for IgM antibody was 98.0%, 98.0%, and 97.0%, and the specificity for IgG antibody was identical among the three kits (99.0%). The IgM antibody-positive rates of the three test kits for samples taken at the early stage of the disease (0–4 days after onset) were consistent with all three kits (18.2%); however, the IgM antibody-positive rates thereafter showed considerable differences among the kits, making it difficult to interpret the kinetics of IgM response against SARS-CoV-2. The IgG antibody-positive rates for samples taken after 13 days of onset were 100.0%, 97.6%, and 97.6%, respectively. Conclusion: There were large differences among the results of the three test kits. Only few cases showed positive results for IgM, suggesting that at least 2 of these kits used in this study were unsuitable for diagnosis of COVID-19. The IgG antibody was positive in almost all samples after 13 days of onset, suggesting that it may be useful for determining infections in the recent past. Abstract : SARS-CoV-2; COVID-19; Antibody; Immunochromatography; Infectious disease; Virology; Immunology; Laboratory medicine; Diagnostics.